(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The word ’Fair’ itself suggests its meaning. People think of games, rides, toys, crafts, furniture, textiles etc. through this word. Here I am going to discuss on the ’Fine Arts Fair’ of Faculty of Fine Arts, The M.S. University of Baroda. Prof. K. G. Subramanian (Padma Bhushan and Padma Vibhushan and Padma Shri awardee) started this tradition. His original idea of introducing this fair was to learn and explore new materials as well as various production techniques of art and craft and then bringing them into art and design. I will discuss various learning processes through ’Fine Arts Fair’ and how artists and designers have adopted it in their works through specific case studies. I will also throw the light on how this fair helps to bridge the gap between common and creative people.